Strategies in Introduction Emergent Literacy for Early Childhood in Early Childhood Education - Hidayati, Novi; Meliani, Fitri; Yuliyanto, Aan; Sofiasyari, Irma; Muzfirah, Suci (KINDERGARTEN: Journal of Islamic Early Childhood Education, 2023)
This research is motivated by the low interest in literacy in children and the demands from parents for children to be proficient in reading and writing. So, this study aims to analyze the strategies used by educators in introducing early literacy in early childhood. This study used a qualitative case study method with four early childhood education teachers at PAUD Purwakarta as subjects. This data collection technique uses interviews. The results of the interview will be analyzed using Grounded Theory analysis. This data analysis uses three stages, namely open coding, axial coding, and selective coding. The results of this study are the strategies used by educators in introducing literacy to early childhood, such as creating an environment rich in children's literacy including labeling each object, providing wall pictures or writing, and providing a reading corner. Then, prohibiting literacy through reading materials includes selecting books or reading materials, involving children in reading activities, and sharing writing experiences. Not only that, but educators also provide strategies through games, songs, and movements, as well as role-playing.